2011
DOI: 10.1080/10496505.2011.563223
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Locally Produced Organic Foods in Three Metropolitan Arkansas Farmers’ Markets: Consumer Opinions and Food Safety Concerns

Abstract: Consumers embrace local food systems as an alternative to the global corporate model, and nearly 75% of consumers in the United States purchase organic foods occasionally. To assess consumers' knowledge of locally grown organic foods, surveys were administered at three metropolitan farmers' markets in Little Rock, Hot Springs, and Texarkana, Arkansas. Consumers with Bachelor's, Associate's, or technical degrees accounted for almost half of the people surveyed. Seventy-one percent believed organic foods were sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 7 publications
2
13
0
Order By: Relevance
“…Additionally, the study showed that the income levels and employment status between shoppers and nonshoppers was similar (Wolf et al, 2005). A study by Rainey et al (2011) obtained similar results. The study also showed that many consumers shop for local produce at farmers' markets (61%) and supermarkets (62%).…”
Section: Introductionsupporting
confidence: 64%
“…Additionally, the study showed that the income levels and employment status between shoppers and nonshoppers was similar (Wolf et al, 2005). A study by Rainey et al (2011) obtained similar results. The study also showed that many consumers shop for local produce at farmers' markets (61%) and supermarkets (62%).…”
Section: Introductionsupporting
confidence: 64%
“…The survey questions for the present study were developed based on the reported findings about GFSI, our previous surveys (1,8,13,14), and input from knowledgeable food safety professionals from academia, quality managers working in the food industry, and professional auditors for food safety certifica tion programs. The questions were beta tested with a diverse group of suppliers (n = 17) who produce food products from various food categories and represent companies of various sizes.…”
Section: A Ter Ia Ls a N D M E T H O D Smentioning
confidence: 99%
“…Consumer perception of these foods as " healthier," as well as the " social" aspects, such as being locally grown or produced in clean and sustainable environments, have considerably increased the demand for organic foods (6,14,24). In terms of market trends, the sales of organic food and beverages in the United States have risen from $1 billion in 1990 to $26.7 billion in 2010, with 7.7% growth in sales over the 2009 figures (23).…”
mentioning
confidence: 99%